NIKAH SIRRI PERSPEKTIF HUKUM ISLAM - Maloko, M. Thahir (Sipakalebbi, 2014)
Â Â This paper explores âUnregistered Marriage from Islamic Law Perspective (an Analysis of Islamic Law Compilation)â in which has three concerns; (1) What is the Islamic perspective regarding to unregisterd marriage? (2) What factors are contributed to unregistered marriage, (3) what are the implications of unregistaered marriage on the couple and their family. It can be concluded that unregistered marriage is legal according to Islamic Law if it fulfill marriage requirement. Factors related unregistered marriage are econonomic and social status as well as moral deviciency. The implications of such marriega are; (1). Marriage is illegal as it is not registered formally at the religious office (KUA) although it is legal according to Islamic law. (2). The child has only legally connected to motherâs heredity, not from fatherâs side. As the marriage is not registered, the child is not formally registered under the fartherâs family and it is against human rights. (3). For further implication, wife and child have no rights to claim economic support and other support from the man. Tulisan ini membahas tentang âNikah Sirri dalam Perspektif Hukum Islam (Telaah Terhadap Kompilasi Hukum Islam)â, dengan mengungkapkan masalah, yaitu: (1) Bagaimana nikih sirri dalam perspektif hukum Islam, (2) Faktor-faktor apa saja yang melatar belakangi sehingga terjadinya nikah sirri, dan (3) Bagaimana dampak yang ditimbulkan bagi orang yang melakukan nikah sirri terhadap diri dan keluarganya. Nikah sirri dalam perspektif hukum Islam adalah sah apabila memenuhi rukun dan syarat nikah. Adapun penyebabnya antara lain: faktor ekonomi, status sosial, dan krisis akhlak. Sedangkan dampak yang akan timbul dari perkawinan yang tidak dicatatkan secara yuridis formal: (1) Perkawinan dianggap tidak sah, meskipun perkawinan dilakukan menurut agama dan kepercayaan, namun dimata negara perkawinan tersebut tidak sah jika belum dicatat oleh KUA atau Kantor Catatan Sipil (KCS), (2) Anak yang lahir dari perkawinanan tersebut hanya mempunyai hubungan perdata dengan ibu dan keluarga ibu. (3) Akibat lebih jauh dari perkawinan yang tidak tercatat adalah, tidak berhak menuntut nafkah atau warisan dari ayahnya.